2009
DOI: 10.1111/j.1537-2995.2009.02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial C antigen in sickle cell disease patients: clinical relevance and prevention of alloimmunization

Abstract: This study demonstrates the need to detect partial C within C+ SCD patients and to prevent immunization. A larger number of Afro-Caribbeans donors is needed to provide these patients with C- RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 16 publications
4
65
2
Order By: Relevance
“…A previous study showed that the C antigen should always be evaluated for a partial variant in SCD patients. 11 In patient 3, a complex combination of rare alleles was found but was not involved in the index DHTR. Finally, patient 8, who had a weak D type 4, developed anti-D antibodies after receiving a single D+ unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the C antigen should always be evaluated for a partial variant in SCD patients. 11 In patient 3, a complex combination of rare alleles was found but was not involved in the index DHTR. Finally, patient 8, who had a weak D type 4, developed anti-D antibodies after receiving a single D+ unit.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] DHTR has been reported to occur in 4-11% of SCD patients given blood transfusions. 6,[10][11][12] DHTRs occur from a few days to two weeks after a blood transfusion and manifest as clinical features of acute hemolysis (hemoglobinuria, jaundice, and pallor) combined with symptoms suggesting severe vaso-occlusive crisis (pain, fever, and sometimes acute chest syndrome). The destruction of both the donor's and the recipient's RBCs leads to an abrupt drop in the hemoglobin level, to a value lower than the pre-transfusion value.…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot exclude that non-extended matching has been applied in some cases due to lack of time or limited supply in acute situations, these numbers do provide insight in the effectiveness of extended matching policies in daily practice. Alternatively, the substantial number of Rh antibodies found may also be explained by diversity in the RH locus in the SCD population [25,26]. Variant alleles encoding altered or partial Rh antigens, not detected by routine serologic testing, are highly prevalent in the population from African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,23 Importantly, Rh antibodies continue to occur in patients who receive donor units that are antigen-matched by serology for Rh D, C, and E antigens because of RH variation at the genetic level. We previously reported that individuals who express only altered or partial Rh antigen (and no corresponding conventional protein) are at increased risk of alloimmunization.…”
Section: Discussionmentioning
confidence: 99%